Pengembangan Media Interaktif Pada Materi Geometri dengan Website Berbasis Geogebra Siswa Kelas IX di SMPN 9 Mataram - Fadila, Kasturi Anisa; Amrullah, Amrullah; Primajati, Gilang; Hikmah, Nurul (FKIP Universitas Mataram, 2025)
This study is motivated by the number of students who have difficulty in understanding geometric transformation material, this can be seen from the low daily test results, lack of understanding of basic concepts, inability to solve varied problems, and difficulty in determining coordinates appropriately. One of the main factors causing these problems is the lack of use of interactive learning media that can actively involve students in the learning process, as well as the dominance of conventional learning methods. This research aims to develop interactive media with a geogebra-based website that is valid and practical. This research uses the ADDIE development model which consists of five stages: analysis, design, development, implementation and evaluation. Data collection techniques include observation, interview, validation questionnaire, and practicality questionnaire. The validation questionnaire was analyzed using Aiken's V formula, while the practicality was analyzed using the practicality score. The developed media has been tested on students of class IX-A at SMPN 9 Mataram. The results showed that the interactive media with a geogebra-based website was included in the very valid category with a score of 84.5% and very practical with a score of 94.2%.